(untitled) (Biological Sciences - PJSIR, 2003)
Karanjin was isolated from Tephrosia purpurea and formu- lated as a 3-methoxy-8-phenylfuro [2, 3-h] benzopyran-6-one (7) on the basis of spectral data (Sinha et al 1982) but no synthetic proof was provided. The chalcone (5) was obtained by the aldol condensation of 5-acetyl-4-hydroxybenzofuran (4) with benzaldehyde. b-Resacetophenone (Clarke 1955) (1) when refluxed with allyl bromide in presence of potassium carbonate and acetone yielded 4-O-allylresacetophenone (Rangaswarnis et al 1954) (2) which on Claisen migration gave 3-C-allylrescetophenone (Baker and Lothin 1935) (3). This was subjected to OsO4/KIO4 oxidation followed by orthophosphoric acid cyclizatin to (Naik et al 1975) (4). Per- oxide treatment of (5) gave the flavone (6) which on selective methylation afforded karanjin (7).